2015
DOI: 10.1021/acs.jpcb.5b08245
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Topology and Local Dynamics Govern the Viscosity of Imidazolium-Based Ionic Liquids

Abstract: A series of branched ionic liquids (ILs) based on the 1-(iso-alkyl)-3-methylimidazolium cation from 1-(1-methylethyl)-3-methylimidazolium bistriflimide to 1-(5-methylhexyl)-3-methylimidazolium bistriflimide and linear ILs based on the 1-(n-alkyl)-3-methylimidazolium cation from 1-propyl-3-methylimidazolium bistriflimide to 1-heptyl-3-methylimidazolum bistriflimide were recently synthesized and their physicochemical properties characterized. For the ILs with the same number of carbons in the alkyl chain, the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 45 publications
3
62
0
Order By: Relevance
“…The relatively high viscosity for these ILs compared with their n -alkyl homologous depends heavily on the reorientation motion on ILs. Maginn and co-workers[28], based on the unpublished data by Xue et al [31], reported higher viscosities for branched aromatic ILs. According to the simulation study carried by the authors[28] these results were explained by a higher packing stability of the ion pairs in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high viscosity for these ILs compared with their n -alkyl homologous depends heavily on the reorientation motion on ILs. Maginn and co-workers[28], based on the unpublished data by Xue et al [31], reported higher viscosities for branched aromatic ILs. According to the simulation study carried by the authors[28] these results were explained by a higher packing stability of the ion pairs in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…In two component ionic liquids, hydrogen bonding and salt bridges 29 as well as molecular stacking due to side chain length30 have been identified as viscosity contributors. Analogous to having a larger population of acid (non-charged) species in single…”
mentioning
confidence: 99%
“…Rather, we suggest that the difference is due to a steric effect. Quantum chemistry calculations indicate that in the lowest energy configurations of [C n C 1 im] + cations, the linear alkyl chain is fully extended from the imidazolium ring . In contrast, in the lowest energy configuration of [BnzC 1 im] + , the phenyl ring and imidazolium ring of the [BnzC 1 im] + are oriented perpendicular to each other .…”
Section: Discussionmentioning
confidence: 99%